Sporadic Cryptosporidiosis Case-Control Study with Genotyping - Hunter, Paul R. (Centers for Disease Control and Prevention, 2004)
We report a case-control study of sporadic cryptosporidiosis with genotyping of isolates from case-patients. A postal questionnaire was completed by 427 patients and 427 controls. We obtained genotyping data on isolates from 191 patients; 115 were Cryptosporidium hominis, and 76 were C. parvum. When all cryptosporidiosis cases were analyzed, three variables were strongly associated with illness: travel outside the United Kingdom, contact with another person with diarrhea, and touching cattle. Eating ice cream and eating raw vegetables were both strongly negatively associated with illness. Helping a child <5 years of age to use the toilet and the number of glasses of tap water drunk at home each day were also independently positively associated with risk. Eating tomatoes was negatively associated. For C. hominis infections, the strongly significant risk factors were travel abroad and changing diapers of children <5 years of age. For C. parvum, eating raw vegetables and eating tomatoes were strongly negatively associated with illness; touching farm animals was associated with illness.